The Difficulties of Theoretical and Applied Learning for Mathematics Subject in Primary Schools - ALSHATRI, Shwan H. H.; WAKIL, Karzan; BAKHTYAR, Ribwar (International e-Journal of Educational Studies, 2019)
Mathematics one of the important subject in primary schools, it is the best criteria for evaluating the ability of students level for learning and understanding. The problem is the students felt weakness and anxious in mathematics subject especially those students in the grade one to three, moreover, sometimes they fail in mathematics become to a factor to fail other scientific subjects, for these reasons the teachers should be teaching mathematics carefully and use modern methodologies for teaching mathematics. This study aims to find the factor of difficulties of teaching mathematics in the primary classes as well as the complexities in the mathematics curriculum in these classes. For addressing this issue, we use a sampling method for collecting data and analyzing method for analyzing data collected. For collecting real data, ten relative questions proposed then answered by one hundred teachers through their experience and their knowledge. The result of the study shows that the mathematics subject needs to improve through teachers’ experience and to improve the mathematics curriculum. Moreover, this results leads for the teachers to solve general issues of mathematics in the primary school, especially among grade one to grade three. Mathematics one of the important subject in primary schools, it is the best criteria for evaluating the ability of students level for learning and understanding. The problem is the students felt weakness and anxious in mathematics subject especially those students in the grade one to three, moreover, sometimes they fail in mathematics become to a factor to fail other scientific subjects, for these reasons the teachers should be teaching mathematics carefully and use modern methodologies for teaching mathematics. This study aims to find the factor of difficulties of teaching mathematics in the primary classes as well as the complexities in the mathematics curriculum in these classes. For addressing this issue, we use a sampling method for collecting data and analyzing method for analyzing data collected. For collecting real data, ten relative questions proposed then answered by one hundred teachers through their experience and their knowledge. The result of the study shows that the mathematics subject needs to improve through teachers’ experience and to improve the mathematics curriculum. Moreover, this results leads for the teachers to solve general issues of mathematics in the primary school, especially among grade one to grade three.